Simply starters! : healthy, non-fried appetizers - Saraf, Shakuntala; Shah, Nimesh (Mumbai : Vakils, Feffer & Simons, 2008)
Features of unusual non-fried starters, step by step guidelines and tips for food presentation
Keywords: Cookery; Appetizers